2023
DOI: 10.3390/f14061126
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of AMF Inoculation and Boron Deficiency on the Growth and Physiology of Camellia oleifera Seedlings

Abstract: Arbuscular mycorrhizal fungi (AMF) symbiosis has been shown to improve the ability to obtain nutrients and resist adverse environmental conditions. However, there are few studies on the functions of AMF in the absorption and accumulation of boron (B). Moreover, it is still unclear whether the root colonization rates of AMF are limited by B deficiency. In this study, Camellia oleifera seedlings were planted in normal and boron-deficient substrates, and the seedlings were inoculated with Funneliformis mosseae or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…cv. Chang Lin 40) seedlings ( Liu et al., 2023 ). AMF have also been shown to increase the availability of Fe in the soil by stimulating the secretion of phenolic acids from the roots of quince ( Cydonia oblonga Mill.…”
Section: Discussionmentioning
confidence: 99%
“…cv. Chang Lin 40) seedlings ( Liu et al., 2023 ). AMF have also been shown to increase the availability of Fe in the soil by stimulating the secretion of phenolic acids from the roots of quince ( Cydonia oblonga Mill.…”
Section: Discussionmentioning
confidence: 99%
“…The trace element boron has been shown to be essential for woody plants overcoming stress conditions [21]. Liu et al uncovered the effects of Funneliformis mosseae inoculation on C. oleifera seedlings under normal and boron deficient conditions and found that AMF inoculation improves boron deficiency resistance and that AMF colonization is influenced by boron availability [22].…”
Section: Nutrientmentioning
confidence: 99%